BDNF-mediated regulation of GSK-3β and PSD95 phosphorylation in anti-depressive effects of Capsosiphon fulvescens glycoproteins against chronic alcohol exposure - Jeong Hwan Oh; Taek-Jeong Nam (Journal of Functional Foods)
Hydrophilic glycoproteins from the alga Capsosiphon fulvescens (Cf-hGP) enhance spatial memory and reduce depression-like behavior in aging rats. However, their effects on ethanol-induced depression-like behavior in adolescent rats and underlying mechanisms remain unclear. This study investigated the neuroprotective effects of Cf-hGP in mitigating depression-like behavior caused by chronic alcohol administration (2 g/kg, 4 weeks) in rats, focusing on molecular changes in the ventral hippocampus. Chronic alcohol exposure increased glucose-regulated protein 78 (an ER stress marker), while decreasing brain-derived neurotrophic factor (BDNF) and phosphorylation of glycogen synthase kinase 3-beta (GSK-3β; Ser9) and postsynaptic density protein 95 (PSD95; Ser295). Cf-hGP administration (10 mg/kg/d) reversed these effects, restoring GSK-3β and PSD95 phosphorylation. Blockade of BDNF signaling suppressed Cf-hGP’s effects, confirming its role in BDNF-mediated neuroprotection. Cf-hGP also reduced alcohol-induced depression-like behavior, suggesting its potential as a therapeutic agent for alcohol-induced depression via modulation of ER stress and BDNF signaling pathways.